Odor-mediated behavioral responses of hatchery-reared blue swimming crab portunus pelagicus (Malacostraca, Decapoda) instars exposed to various chemical cues - Ledesma, Anne Brigette B.; Monteclaro, Harold M. (2018)
In this study, the ability of hatchery-reared blue swimming crab Portunus pelagicus instars to discriminate various odors was tested in a y-maze aquarium using the following chemical cues: 1) mussel odor, 2) snapper odor, 3) combination of mussel and snapper odors, and 4) seawater as control. Results showed that when given a choice between seawater and mussel odor, a higher percentage of instars preferred to stay along the mussel odor stream. In contrast, avoidance response was elicited when snapper odor was introduced to crab instars. When provided with a choice between mussel odor and snapper odor, the instars exhibited preference to the former. However, when presented with a combination of two conflicting odors (mussel and snapper odors), the crab instars favored to stay in the control chamber. These results suggest that even at its early developmental stage, blue swimming crab instars are highly responsive and can distinguish food from alarm odors, such as those odors coming from perceived potential predators. This study is important in understanding the behavioral capacities of hatcheryreared animals, their responses when released to a new and harsh environment, and possible applications of these behaviors in enabling restocking programs feasible.
Includes bibliographical references (pages 228-229)
Keywords: Marine science; Alarm odor; Chemoreception; Portunus pelagicus; Crab instars; Hatchery-reared blue swimming crab